Characterizations of a helix in the pseudo - Galilean space G31 - Kulahci, Mihriban (Academic Journals, 2010)
In this manuscript, we obtained some characterizations for a helix in the pseudo-Galilean space G(3)(1).
Keywords: Pseudo-Galilean space; helix; position vector